KEMAMPUAN LITERASI SAINS PESERTA DIDIK KELAS XI MIPA SMA NEGERI 8 BONE PADA MODEL DL MATERI KOLOID - NOVITA SARI; HALIMAH HUSEIN; MUHAMMAD ANWAR (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study aims to determine the scientific literacy skills of students after studying colloidal material through Model Discovery learning. This study uses a One-Shot Case Study research design with the research subjects used are students of class XI MIPA 3 which consists of 30 students. Data collection was carried out by providing valid scientific literacy test instruments to research subjects and observing student activities. Research results obtained in general the scientific literacy profile of students XI MIPA 3 SMAN 8 Bone is in the category enough with an average value of 64.03%. Dimensional science literacy skills context with personal indikators obtained a value of 56.11% with sufficient category, social indikators with a value of 63.94% with sufficient categories and global indikators with good category. Overall the average value of the context dimension is 67.05% with sufficient category. On the knowledge dimension with content indikators obtained a value of 64.76% with sufficient category, procedural indikators obtained a value of 60% with less category and epistemik indikators obtained a value of 70% with Sufficient category. Overall the average value of the knowledge dimension is 64.92 with sufficient category. On the competency dimension with indikators explain the phenomenon scientifically obtained a value of 55.00% with the category lacking, indikators of evaluating and designing scientific investigations are obtained a value of 68.33% with a sufficient category, and indikators interpret data and evidence scientifically obtained a value of 67.77% with sufficient category. Overall the average value of the competency dimension is 63.7% with sufficient category. ABSTRAKPenelitian ini bertujuan untuk mengetahui kemampuan literasi sains peserta didik setelah mempelajari materi koloid melalui pembelajaran Model Discovery. Penelitian ini menggunakan desain penelitian One-Shot Case Study dengan subjek penelitian yang digunakan adalah peserta didik kelas XI MIPA 3 yang terdiri dari 30 peserta didik. Pengumpulan data dilakukan dengan memberikan instrumen tes kemampuan literasi sains yang valid kepada subjek penelitian dan melakukan observasi aktivitas peserta didik. Hasil penelitian yang didapatkan secara umum profil literasi sains peserta didik XI MIPA 3 SMAN 8 Bone berada pada kategori cukup dengan nilai rata-rata sebesar 64,03%. Kemampuan literasi sains dimensi konteks dengan indikator personal diperoleh nilai 56,11% dengan kategori cukup, indikator social dengan nilai 63,94% dengan kategori cukup dan indikator global dengan kategori baik. Secara keseluruhan nilai rata-rata dimensi konteks 67,05% dengan kategori cukup. Pada dimensi pengetahuan dengan indikator konten diperoleh nilai 64,76% dengan kategori cukup, indikator prosedural diperoleh nilai 60% dengan kategori kurang dan indikator epistemik diperoleh nilai 70% dengan kategori cukup. Secara keseluruhan nilai rata-rata dimensi pengetahuan yaitu 64,92 dengan kategori cukup. Pada dimensi kompetensi dengan indikator menjelaskan fenomena secara saintifik diperoleh nilai 55,00% dengan kategori kurang, indikator mengevaluasi dan merancang penyelidikan ilmiah diperoleh nilai 68,33% dengan kategori cukup, dan indikator menafsirkan data dan bukti secara ilmiah diroleh nilai 67,77% dengan kategori cukup. Secara keseluruhan nilai rata-rata dimensi kompetensi yaitu 63,7% dengan kategori cukup.